# calc

posted by .

how would i find the derivative of these?

f(x)=ln((√x)+1)

and

f(x)=ln(x+1/x-1)

thank u!!

• calc -

first one:
remember that √x = x^(1/2)

f ' (x) = 1/(√x + 1) ( (1/2)x^(-1/2)
= 1/( 2x^(1/2) (√x)(√x + 1)
= 1/( 2√x(√x + 1) or 1/(2(x+√x)

2nd:

not clear if you meant
ln( x + 1/x - 1) --- the way you typed it , or
ln( (x+1)/(x-1) ) --- I have a feeling that's the one, or
ln( x + 1/(x-1) )

I will read it as ln ((x+1)/(x-1))
then this can be changed to
ln(x+1) - ln(x-1)
f ' (x) = 1/(x+1) - 1/(x-1)
= (x-1 - (x+1))/((x+1)(x-1))
= -2/((x+1)(x-1))

notice how important brackets are ?

## Similar Questions

1. ### Algebra

How would i complete these problems? 1. (√6mn)^5 2. ^3√16x - ^3√2x^4 3.^4√x • ^3√2x 4. ^3√72x^8 5. √63a^5b • √27a^6b^4 and are these problems correct?
2. ### Math

Find an equation of the line that bisects the obtuse angles formed by the lines with equations 3x-y=1 and x+y=-2. a. (3√2 +√10)x-(√10 + √2)y-2√10+√2=0 b. (3√2 - √10)x+(√10 - √2)y+2√10+√2=0 …
3. ### Calculus

y=(√x)/((√x)+1) Find the concavity and point of inflection(s). y'=1/(√(x/2))(√x+1)² y'=1/(x√(x/2)+2√(x²/2)+√(x/2)) y"=0- ?
4. ### Algebra 2 Answer Check

Simplify by rationalizing each denominator. 1. 2/√3 A: 2√3 / 3 2. -18/√6 A: -3√6 Add or subtract. 3. 4√3 - 9√3 A: -5√3 4. √8 - 15√2 A: -13√2 5. √45 + √20 A: 5√5 …
5. ### Calculus

How would I find the second derivative if f(x)= √(x^3+2) using the quotient rule. I got to the step where [(12x√(x^3+2))-(9x^4/√(x^3+2))]/4(x^3+2) how would i go from that to: (3x(x^3+8))/(4(x^3+2)^3/2)

Can you check my answers? 1. 3√20/√4 = 3√(5)(4)/2 = 3(2)√5/2 = 3√5 2. 4√15/√9 = 4√15/3 3. √12/√16 = √4(3)/4 = 2√3/4 = √3/2 4. √10/√5 = √2
7. ### Math

Could I please get some help for these 3 questions, apologies for asking so many, but they were the ones I was really unsure of: 1. Find an equation for the line tangent to y=ln(x) and that goes through the origin. I have no idea, …
8. ### Calc 1

√1+t-√1-t/t lim -----> 0 The answer is one and I am not getting it I factored it like this √1+t-√1-t/t x √1+t-√1-t Factoring it out further I got in the numerator (1-t)(1+t) / t(√1+t+√1-t) …
9. ### Algebra

1. Simplify the expression: 4√18+5√32 A.45√2 B.32√2 C.116√2 D.9√50 2. Simplify the expression: 7√5-3√80 A.-5√5 B.-4√75 C.-5 D.4√-75 3. Simplify the expression: √21(√3+√14) …
10. ### Algebra - Check My Work

For Question 1-8 Simplify the Radical Expression *** - My Answer 1.√45 3√5*** 2.√180x^2 6x√5*** 3.√150x^3 k^4 5xk^2√6x*** 4.√21y * 5√49y 35y√21*** 5.(The square root sign applies …

More Similar Questions